2021
DOI: 10.1016/s2213-2600(20)30566-x
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon lambda for the treatment of outpatients with COVID-19: a phase 2, placebo-controlled randomised trial

Abstract: Background To date, only monoclonal antibodies have been shown to be effective for outpatients with COVID-19. Interferon lambda-1 is a type III interferon involved in innate antiviral responses with activity against respiratory pathogens. We aimed to investigate the safety and efficacy of peginterferon lambda in the treatment of outpatients with mild-to-moderate COVID-19. MethodsIn this double-blind, placebo-controlled trial, outpatients with laboratory-confirmed COVID-19 were randomly assigned to a single sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
175
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(196 citation statements)
references
References 41 publications
(37 reference statements)
2
175
0
2
Order By: Relevance
“…Matched plasma and dried blood spots were also collected from 52 PCR-positive confirmed patients, 90 days or greater from diagnosis, and 11 healthy controls ( Table S2 ). These 52 patients were recruited from a phase II randomized clinical trial of COVID-19 treatment [ 33 ]. Blood was collected by finger prick to fill the spots on a Whatman 903 Protein Saver card.…”
Section: Methodsmentioning
confidence: 99%
“…Matched plasma and dried blood spots were also collected from 52 PCR-positive confirmed patients, 90 days or greater from diagnosis, and 11 healthy controls ( Table S2 ). These 52 patients were recruited from a phase II randomized clinical trial of COVID-19 treatment [ 33 ]. Blood was collected by finger prick to fill the spots on a Whatman 903 Protein Saver card.…”
Section: Methodsmentioning
confidence: 99%
“…This has led the WHO to recommend against its use in COVID-19 [13]. Indeed, no antiviral small molecule drug has yet shown life saving benefit in COVID-19 infections, nor is there any definitive evidence yet that any antiviral drugs accelerate viral clearance [14], although a randomised placebo controlled trial of peginterferon lambda (a large molecule biological antiviral) in 60 COVID-19 outpatients showed greater viral decline in the peginterferon group [15]. We note that the primary endpoint in this trial was the proportion qPCR negative 7 days after enrolment, an endpoint which has the same disadvantages as time to clearance.…”
Section: Discussionmentioning
confidence: 99%
“…We note that the primary endpoint in this trial was the proportion qPCR negative 7 days after enrolment, an endpoint which has the same disadvantages as time to clearance. In addition, 15 out of the 60 patients had undetectable virus at baseline [15] emphasising the need to select patients shortly after symptom onset. The final analysis did adjust for baseline viral load but most studies describing viral clearance ‘rates’ are reporting the time to a negative nasopharyngeal swab without adjustment for the baseline viral load.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative suggested by the IRAP model might be to stimulate a natural interferon release using RIG1, NOD1 and, perhaps, TLR3 agonists (Figure 12). Indeed, a just-released clinical study demonstrated that COVID-19 patients treated with the hepatitis drug peg-interferon are four times more likely to recover quickly and clear their SARS-CoV-2 infection than equivalently treated patients not given that drug [273].…”
Section: Implications Of Innate Receptor Activation Profiles For Tretmentioning
confidence: 99%